MicroRNAs regulating apoptosis and delivery strategies for treating intervertebral disc degeneration - Chen, Yuwei; Guo, Chuan; Lan, Weiqiang; Liu, Yuheng; Ma, Fei; Zheng, Daqiang; Xu, Xueyuan; Kong, Qingquan; Wang, Yu (Frontiers in Cell and Developmental Biology, 2025)
Intervertebral disc degeneration (IDD) is a leading contributor to chronic low back pain (LBP), significantly impairing quality of life and imposing socioeconomic burdens globally. Current treatments fail to address the underlying pathology or restore intervertebral disc (IVD) function. IDD is multifactorial but strongly linked to nucleus pulposus cell (NPC) apoptosis. Gene therapy, particularly the use of microRNAs (miRNAs), holds promise for reversing IDD by targeting apoptotic pathways and enhancing the biological functions of NPCs. Given the avascular nature of IVD, effective delivery strategies are critical. Targeting strategies, such as NPC-targeting, which relies on cellular uptake through direct uptake, specific ligand‒receptor interactions and aptamer utilization, can significantly increase delivery efficacy. Additionally, organelle-targeting strategies that focus on mitochondria and the endoplasmic reticulum (ER) optimize therapeutic delivery. Coupled with these targeting methods, responsive delivery strategies that react to endogenous stimuli (such as pH, reactive oxygen species, and enzymes) and exogenous stimuli (including temperature, ultrasound, magnetism, and light) enable spatiotemporal release of therapeutic agents. This review summarizes the role of anti-apoptotic miRNAs in regulating NPC apoptosis and the latest advances in targeting and responsive delivery strategies to overcome the challenges associated with targeted therapeutic miRNA application, offering new insights into the treatment of IDD.